Critical thinking skills for your social work degree - Bottomley, Jane; Cartney, Patricia; Pryjmachuk, Steven (Critical study skills, 2019)
An essential text for all those undertaking a social work degree within higher education, providing study support and skills development for critical thinking, reading and writing.